Manufacturing method for bonded metal parts

By coating a bonding member with a non-eluting material and selectively etching the metal bonding phase within the cemented carbide alloy, the method addresses the challenge of incomplete corrosion in bonded metal parts, achieving improved wear and adhesion resistance.

JP7659826B2Active Publication Date: 2025-04-10KYUSHU MIZUHO CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022066422
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-04-13
Publication Date
2025-04-10
Estimated Expiration
2042-04-13

AI Technical Summary

Technical Problem

Existing methods for manufacturing bonded metal parts fail to effectively corrode the metal bonding phase of carbide alloys due to differences in ionization tendency, leading to incomplete improvement of properties such as wear resistance and adhesion resistance.

Method used

A method involving the coating of a bonding member with a non-eluting material, followed by selective etching of the metal bonding phase within the cemented carbide alloy, allowing for targeted corrosion of the metal bonding phase while preventing corrosion of the bonding member.

Benefits of technology

This method enables the intended corrosion of the metal bonding phase, thereby enhancing the properties of bonded metal parts, such as wear resistance and adhesion resistance, while maintaining the strength of the bonding member.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659826000005
    Figure 0007659826000005
  • Figure 0007659826000006
    Figure 0007659826000006
  • Figure 0007659826000007
    Figure 0007659826000007
Patent Text Reader

Abstract

To provide a manufacturing method of a junction type metal component that makes it possible to perform corrosion of a metal bond phase of a hard metal as intended, even if a junction type metal components manufactured by joining a joint member formed by an alloy having, as a host phase, a metal having a larger ionization tendency than a host phase of a metal bond phase of a hard metal constituting a hard metal member with respect to a hard metal alloy member formed by the hard alloy.SOLUTION: For a junction type metal component manufactured by joining a junction member 4 formed of an alloy having, as a host phase, a metal that has a greater ionization tendency than a host phase of a metal bond phase of the hard metal that constitutes the hard metal member 3 to a hard metal member 3 formed of a hard metal, a bonding member 4 is coated with a non-eluting material, and then only the metal bond phase among a hard particle phase and the metal bond phase contained in the hard metal constituting a hard metal member 3 is selectively etched to apply a surface treatment.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing a bonded metal component by joining a bonding member formed of an alloy having a parent phase of a metal having a higher ionization tendency than the parent phase of the metallic bonding phase of the cemented carbide constituting the cemented carbide member to a cemented carbide member formed of a cemented carbide. [Background technology]

[0002] In recent years, with regard to improving the properties of cemented carbide tools used as cutting tools, it has been reported in Patent Document 1 that by removing the metallic binder phase from the surface of a cemented carbide alloy consisting of a hard particle phase and a metallic binder phase and leaving only the hard particle phase on the surface and using the tool as such, properties such as wear resistance and adhesion resistance can be improved.

[0003] The metallic bonding phase is removed by chemical etching or physical etching. For example, Patent Document 2 discloses a process for removing the surface metallic bonding phase using aqua regia or nitric acid solution. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] WO2019 / 065677 publication [Patent Document 2] JP 2019-206754 A Summary of the Invention [Problem to be solved by the invention]

[0005] When the processes described in Patent Documents 1 and 2 are applied to a bonded metal component manufactured by bonding a bonding member formed from an alloy having a parent phase of a metal with a higher ionization tendency than the parent phase of the metallic bonding phase of the cemented carbide constituting the cemented carbide component to a cemented carbide component, a situation occurs in which, due to the difference in ionization tendency, only the bonding member formed from the alloy having a parent phase of a metal with a higher ionization tendency is etched, and corrosion of the metallic bonding phase of the cemented carbide constituting the cemented carbide component does not progress.

[0006] For example, in a metal wire drawing process, in a composite die in which an iron alloy used as an outer diameter retaining ring is joined to an inner diameter cemented carbide die, when attempting to etch the inner diameter cemented carbide, due to the difference in ionization tendency, only the outer diameter iron alloy ring is etched and corrosion of the metallic bonding phase in the inner diameter cemented carbide does not progress.

[0007] Under such circumstances, the corrosion of the metal bonding phase of the cemented carbide cannot be carried out as intended, and it is not possible to achieve improvements in properties such as wear resistance and adhesion resistance in bonded metal parts that include cemented carbide members as their constituent elements.

[0008] The present invention has been made to solve such problems, and has an object to provide a method for manufacturing a bonded metal component which enables corrosion of the metallic bonding phase of the cemented carbide as intended, thereby enabling improvements in properties such as wear resistance and adhesion resistance, even in the case of a bonded metal component manufactured by joining a bonding member formed of an alloy having a parent phase of a metal having a greater ionization tendency than the parent phase of the metallic bonding phase of the cemented carbide constituting the cemented carbide component, to be performed. [Means for solving the problem]

[0009] In order to solve the above problems, the present invention provides a method for manufacturing a bonded metal part by joining a bonding member formed of an alloy having a parent phase of a metal that has a higher ionization tendency than the parent phase of the metallic bonding phase of the cemented carbide constituting the cemented carbide part to a cemented carbide part formed of a cemented carbide, the method being characterized in that the bonding member is coated with a non-eluting material, and then surface treatment is performed by selectively etching only the metallic bonding phase out of the hard particle phase and metallic bonding phase contained in the cemented carbide constituting the cemented carbide part.

[0010] By coating the joining members formed of an alloy having a parent phase of a metal with a higher ionization tendency than the parent phase of the metallic bond phase of the cemented carbide constituting the cemented carbide member with a non-eluting material and then selectively etching only the metallic bond phase out of the hard particle phase and metallic bond phase contained in the cemented carbide constituting the cemented carbide member, it is possible to prevent the occurrence of a situation in which only the joining members formed of an alloy having a parent phase of a metal with a higher ionization tendency progresses in etching due to the difference in ionization tendency, and the corrosion of the metallic bond phase of the cemented carbide constituting the cemented carbide member does not progress. Therefore, it is possible to improve properties such as wear resistance and adhesion resistance.

[0011] In the present invention, the method of joining the joining member to the cemented carbide member can be material joining, chemical joining, or mechanical joining, and can be applied to various joining forms. Therefore, it can be applied to joining type metal parts such as dies and tools for various uses and shapes. Here, material joining is joining that utilizes the characteristics of metal materials, such as welding, brazing, and friction stir welding. Chemical joining is joining that uses adhesives, etc. Mechanical joining is joining by fixing with screws, rivets, etc., or by fitting with press fitting, shrink fitting, etc.

[0012] In the present invention, the depletion depth of the metallic bonding phase when only the metallic bonding phase is selectively etched can be calculated from four pieces of information: the composition of the cemented carbide base, the composition measured by characteristic X-ray analysis from the top surface after the cemented carbide base is processed into a bonded metal part and the metallic bonding phase is selectively etched, the composition of the metallic bonding phase remaining slightly between the hard particles in the depleted region of the selectively etched metallic bonding phase, and the analysis depth measured by the emission of characteristic X-rays in the characteristic X-ray analysis.

[0013] As a result, a small amount of the metallic bond phase remains between the hard particles in the depletion zone after selective etching, and the amount of the metallic bond phase that changes gradually at the interface can be efficiently calculated. Therefore, when a joining member formed of an alloy having a parent phase of a metal with a higher ionization tendency than the parent phase of the metallic bond phase of the cemented carbide constituting the cemented carbide member is coated with a non-eluting material and then surface treatment is performed by selectively etching only the metallic bond phase out of the hard particle phase and metallic bond phase contained in the cemented carbide constituting the cemented carbide member, it becomes possible to accurately calculate the corrosion depth non-destructively. Note that the selective corrosion depth is premised on being approximately the same as the average grain size of the hard particles from the viewpoint of strength retention. Effect of the Invention

[0014] According to the present invention, even in the case of a bonded metal component manufactured by joining a bonding member formed of an alloy having a parent phase of a metal having a greater ionization tendency than the parent phase of the metallic bonding phase of the cemented carbide constituting the cemented carbide component, it is possible to realize a manufacturing method for a bonded metal component that enables corrosion of the metallic bonding phase of the cemented carbide to be carried out as intended, thereby enabling improvement of properties such as wear resistance and adhesion resistance. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a schematic diagram of a shrink-fitted powder compaction die. [Diagram 2] FIG. 13 is a diagram showing the change in a powder molding die before and after etching. [Diagram 3] FIG. 1 is a schematic diagram of a brazed bonded metal part. [Figure 4] FIG. 1 is a diagram showing the change in a bonded metal component before and after etching. [Diagram 5] FIG. 2 is a schematic diagram showing a cross section of the metallic bonding phase on the surface of a cemented carbide member after selective etching and the change in the amount of CO, which is the main component of the metallic bonding phase, during the selective etching. [Figure 6] FIG. 2 is a diagram for defining the depletion depth of a metallic bonding phase. [Figure 7] 1 is a flow chart of a method for measuring the depletion depth of a surface metal binder phase in a cemented carbide. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, a method for producing a bonded metal component according to the present invention will be described based on an embodiment thereof. A first embodiment of a method for producing a bonded metal component will be described with reference to FIG. FIG. 1 is a schematic diagram of a shrink-fitted powder compaction die. The powder molding die is an example of a bonded metal part manufactured by bonding a cemented carbide member 3 formed of cemented carbide to a bonding member 4 formed of an alloy whose parent phase is a metal with a higher ionization tendency than the parent phase of the metallic bonding phase of the cemented carbide constituting the cemented carbide member 3, and material type G3 (classification symbol VM-40) is used for the cemented carbide member 3, and SKD11 is used for the bonding member 4. In cemented carbide, cobalt or nickel is generally used for the metallic bonding phase, and cobalt was selected for the parent phase of the metallic bonding phase of the cemented carbide member 3 material type G3.

[0017] For the powder molding die having this configuration, the joining members 4 were covered with a non-eluting material, and then surface treatment was performed by selectively etching only the metallic bonding phase out of the hard particle phase and metallic bonding phase contained in the cemented carbide constituting the cemented carbide member 3. For comparison, etching treatment was also performed without covering the joining members 4 with a non-eluting material. After the etching treatment, the appearance change was observed, and the change in the metallic bonding phase was analyzed by SEM-EDS. Table 1 shows the results of SEM-EDS analysis of cemented carbide parts using the SU3800 electron microscope.

[0018] [Table 1]

[0019] The results shown in Table 1 show that in the case of etching without a coating, the amount of cobalt in the metallic bonding phase did not change compared to before etching, indicating that no reaction had occurred. In contrast, in the case of etching with a coating, the amount of cobalt in the metallic bonding phase was clearly reduced compared to before etching, indicating that corrosion of the metallic bonding phase had progressed.

[0020] The changes in the powder molding die before and after etching are shown in Figure 2. Figure 2(a) shows the powder molding die before etching, Figure 2(b) shows the powder molding die after etching without being coated with a non-eluting material, and Figure 2(c) shows the powder molding die after etching with a coating of a non-eluting material.

[0021] Comparing Figure 2(a) and Figure 2(b), in Figure 2(b), the outer parts, which are the materials of the joined metal parts, have turned black, indicating that they have been corroded by the etching solution. In contrast, in Figure 2(c), there is no discoloration in the outer parts, which are the materials of the joined metal parts, indicating that they have not been corroded by the etching solution.

[0022] From the above results, it has been demonstrated that in a bonded metal part manufactured by bonding a bonding member 4 formed from an alloy having a parent phase of a metal that has a greater ionization tendency than the parent phase of the metallic bonding phase of the cemented carbide constituting the cemented carbide member 3 formed from cemented carbide, it is possible to suppress corrosion of the bonding member 4 and cause corrosion of the metallic bonding phase of the cemented carbide of the cemented carbide member 3 as intended.

[0023] A second embodiment of the method for producing a bonded metal component will be described with reference to FIG. FIG. 3 is a schematic diagram of a brazed bonded metal part. This brazed bonded metal part is an example of a bonded metal part manufactured by bonding a bonding member 4 formed of an alloy whose parent phase is a metal that has a higher ionization tendency than the parent phase of the metallic bonding phase of the cemented carbide constituting the cemented carbide part 3 to a cemented carbide part 3 formed of cemented carbide. The cemented carbide part 3 is made of material type G5C (classification symbol VM-50), and the bonding member 4 is made of steel S45C.

[0024] For a bonded metal part having this configuration, the bonding members 4 were covered with a non-eluting material, and then surface treatment was performed by selectively etching only the metallic bonding phase out of the hard particle phase and metallic bonding phase contained in the cemented carbide constituting the cemented carbide member 4. For comparison, etching was also performed without covering the bonding members 4 with a non-eluting material. After the etching treatment, the appearance change was observed, and the change in the metallic bonding phase was analyzed by SEM-EDS. Table 2 shows the results of SEM-EDS analysis of cemented carbide parts using the SU3800 electron microscope.

[0025] [Table 2]

[0026] The results shown in Table 2 show that in the case of etching without a coating, the amount of cobalt in the metallic bonding phase did not change compared to before etching, indicating that no reaction had occurred. In contrast, in the case of etching with a coating, the amount of cobalt in the metallic bonding phase was clearly reduced compared to before etching, indicating that corrosion of the metallic bonding phase had progressed.

[0027] The changes in a bonded metal part before and after etching are shown in Figure 4. Figure 4(a) shows the bonded metal part before etching, Figure 4(b) shows the bonded metal part after etching without being coated with a non-eluting material, and Figure 4(c) shows the bonded metal part after etching with a coating of a non-eluting material.

[0028] Comparing Figure 4(a) and Figure 4(b), in Figure 4(b), the joined metal part material has turned black, indicating that it has been corroded by the etching solution, whereas in Figure 4(c), there is no discoloration of the joined metal part material, indicating that it has not been corroded by the etching solution.

[0029] From the above results, it has been demonstrated that in a bonded metal part manufactured by bonding a bonding member 4 formed from an alloy having a parent phase of a metal that has a greater ionization tendency than the parent phase of the metallic bonding phase of the cemented carbide constituting the cemented carbide member 3 to a cemented carbide member 3 formed from cemented carbide, it is possible to suppress corrosion of the bonding member 4 and cause corrosion of the metallic bonding phase of the cemented carbide of the cemented carbide member 3 as intended.

[0030] As described above, the effectiveness of the bonded metal parts manufactured by bonding the bonding member 4 formed of an alloy having a parent phase of a metal with a higher ionization tendency than the parent phase of the metallic bonding phase of the cemented carbide constituting the cemented carbide member 3 to the cemented carbide member 3 has been demonstrated even in bonded metal parts having different bonding methods and shapes. The bonding method of the bonding member 4 to the cemented carbide member 3 can be material bonding, chemical bonding, or mechanical bonding, and can be applied to various bonding forms. Therefore, it can be widely applied to bonded metal parts having different bonding methods and shapes, such as composite dies, composite punches, composite molds, etc.

[0031] Hereinafter, a method for calculating the depletion depth of the selective corrosion of the metallic bonding phase when the metallic bonding phase of the cemented carbide is corroded in the manufacturing method of the bonded metal component of the present invention will be described.

[0032] Figure 5 shows a cross section of the surface of a cemented carbide component after selective etching of the metallic bonding phase, and the C O The graph shows the change in the amount of C in the depleted zone after selective corrosion. OThe amount of C does not become completely zero, but fluctuates. From the area where the metallic bonding phase 2 has been removed by corrosion, the amount of C in the unreacted area changes gradually. O A transition in quantity is occurring and the depletion depth needs to be defined in this region.

[0033] Therefore, the inventors assumed a linear change in composition as shown in FIG. 6 and defined the depletion depth of the metallic bonding phase. O The amount is m1, and the small amount of C remaining between the hard particles O Assume that the amount is m2, m2 and m1 are constant values, and the transition from m2 to m1 is a linear change, as shown in FIG.

[0034] This linear change occurs at C O The transition position of the amount of Co is defined as the depletion depth d of the metallic bonding phase. Using these definitions, the analysis depth D measured by the X-rays irradiated in the characteristic X-ray analysis, and the amount of Co mx actually measured by the characteristic X-ray analysis, an equation is created based on the conservation of mass of the amount of Co, and the following equation (1) is obtained.

[0035]

number

[0036] By solving equation (1) with respect to the depletion depth d, we obtain equation (2).

[0037]

number

[0038] Here, the concentration of the metallic bonding phase remaining between the hard particles must be estimated in advance using an analysis method attached to the scanning electron microscope, etc. The analysis depth is determined by the X-ray intensity of the characteristic X-ray analyzer used and the composition of the cemented carbide to be analyzed.

[0039] Characteristic X-ray analyzers include energy dispersive X-ray analyzers (EDS) and wavelength dispersive X-ray analyzers (WDS). Both instruments measure the chemical composition of a sample by detecting the characteristic X-rays emitted from the sample surface, with EDS measuring the energy of the characteristic X-rays and WDS measuring the wavelength of the characteristic X-rays.

[0040] In the EDS, the reaction region of the characteristic X-rays is relatively shallow at a depth of several μm, whereas the WDS has an analysis depth of more than 10 μm. In the present invention, considering that the material to be analyzed has hard particles with a diameter of about several μm, it can be said that a wavelength dispersive characteristic X-ray analyzer (WDS), which can measure the depth of multiple particles, is a more desirable analytical device.

[0041] Although the impoverishment depth has such a simplified definition, it is arithmetically uniquely determined and always intersects with the transition region of the Co amount, so it is a very easy definition to handle when stating it as a rule in specifications, etc. In addition, because this measurement method is non-destructive, it can be used directly for shipping inspection and can also be used for cause analysis when an abnormality occurs.

[0042] As described above, it is possible to calculate the depletion depth d of the metallic bonding phase from four pieces of information: the composition m1 of the cemented carbide base body, the composition mx measured from the top surface by characteristic X-ray analysis after the same base body is processed into a bonded metal part and the metallic bonding phase is selectively etched, the composition m2 of the metallic bonding phase that remains in small amounts between the hard particles in the depleted area of ​​the selectively etched metallic bonding phase, and the analysis depth D measured by the emission of characteristic X-rays in characteristic X-ray analysis.

[0043] A flow chart of the above-described method for measuring the depletion depth of the surface metallic binder phase in a cemented carbide is shown in Fig. 7. By carrying out this process, even in a situation where the metallic binder phase of the cemented carbide is removed from the surface by etching, the metallic binder phase leaves the hard particle phase in a mesh-like shape and selective corrosion progresses in a tunnel-like shape, the calculated corrosion depth can nondestructively and unambiguously define the depth of the corrosion front, the boundary of which is actually ambiguous.

[0044] A comparison test between the calculated and measured values ​​of the above-mentioned defect depth was carried out for three material types with different grain sizes (fine, medium, and coarse), by producing samples for each of the fine, medium, and coarse grains. The average grain size of each was 0.6 to 1.0 μm for fine grains, 2.0 to 4.0 μm for medium grains, and 5.0 μm or more for coarse grains. The actual measurements were taken at several locations using a wavelength dispersive X-ray analyzer (WDS) and an energy dispersive X-ray analyzer (EDS), and the average values ​​were calculated.

[0045] As a result of the test, the difference between the calculated and measured values ​​of the depletion depth was much smaller than half the particle diameter of the hard particles in all cases of fine, medium, and coarse particles. The value of half the particle diameter of the hard particles can be recognized as a boundary value that determines whether or not the hard particles fall off, and if the difference between the calculated and measured values ​​of the depletion depth exceeds half the particle diameter of the hard particles, it will have a negative effect on the function of the parts made of cemented carbide when selective corrosion is performed. However, according to the test results, the difference between the calculated value of the depletion depth and the measured value is much smaller than half the particle diameter of the hard particles, so it was confirmed that the calculation method of the depletion depth according to the present invention is extremely effective.

[0046] By using this technique, it is possible to accurately calculate the corrosion depth nondestructively when a joining member formed from an alloy whose parent phase is a metal that has a higher ionization tendency than the parent phase of the metallic bonding phase of the cemented carbide that constitutes the cemented carbide member is coated with a non-eluting material and then surface treated by selectively etching only the metallic bonding phase out of the hard particle phase and metallic bonding phase contained in the cemented carbide that constitutes the cemented carbide member. [Industrial Applicability]

[0047] The present invention can be widely used as a manufacturing method for bonded metal parts that can achieve improved properties such as wear resistance and adhesion resistance, because it is possible to intentionally corrode the metallic bonding phase of the cemented carbide, even in cases where the bonded metal part is manufactured by joining a bonding member formed of an alloy having a parent phase of a metal that has a greater ionization tendency than the parent phase of the metallic bonding phase of the cemented carbide that constitutes the cemented carbide part, to a cemented carbide part formed of the cemented carbide. [Explanation of symbols]

[0048] 1 hard particles 2 Metallic bonded phase 3. Cemented carbide components 4 Joining materials

Claims

1. A method for manufacturing a bonded metal part, which is produced by joining a bonding member formed of an alloy having a parent phase of a metal that has a higher ionization tendency than the parent phase of the metallic bonding phase of the cemented carbide constituting the cemented carbide part to a cemented carbide part formed of cemented carbide, characterized in that the bonding member is coated with a non-eluting material, and then, of the hard particle phase and metallic bonding phase contained in the cemented carbide constituting the cemented carbide part, only the metallic bonding phase is selectively etched to perform a surface treatment.

2. 2. The method for manufacturing a bonded metal part according to claim 1, wherein the bonding method of the bonding member to the cemented carbide member is material bonding, chemical bonding, or mechanical bonding.

Citation Information

Patent Citations

  • Dice for cold drawing of pipe

    JP2014018814A

  • Manufacturing method of slide component

    JP2019206754A

  • Cutter protection during leaching process

    US20150014067A1

  • Cutting tool and manufacturing method therefor

    WO2019065677A1